Parasitic Contamination in the Table Vegetables Planted in Shiraz Plain, Iran: Parasitic Contamination of Vegetables in Iran (Biological Sciences - PJSIR, 2010)
Contamination with parasites of the vegetables grown in Shiraz plains and irrigated by urban and industrial sewage-laden Shiraz Rookdhaneh Khoshk River and seasonal Soltanabad River was studied. It was found that 31.5% of the farms irrigated by the river water directly, 30.9% of the farms irrigated by water of nearby located shallow wells and 33.7% of the farms using water from the wells at a distance of one kilometer from the River were contaminated by Ascaris ova. 32.20% vegetables of farms irrigated by the wells located near Soltanabad river were contaminated with insects and larvae and 24.5% with Ascaris worm. After Ascaris ova, the larvae of different insects, Strongyloides parasite, Sterocoralis and Trichostrongylus were the contaminants most present.